Simple and Efficient One-Pot Synthesis of Imidazo[1,2-a]pyridines Catalyzed by Magnetic Nano-Fe3O4–KHSO4·SiO2 - Guntreddi, Tirumaleswararao; Allam, Bharat Kumar; Singh, Krishna Nand (Synlett, 2012)
The present report highlights a magnetic nano-Fe3O4–KHSO4·SiO2 catalyzed synthesis of imidazo[1,2-a]pyridines. The synthetic strategy adopted is expedient, versatile, and offers good to excellent yields from readily available starting materials.
Keywords: multicomponent reactions; transition metals; heterocycles; heterogeneous catalysis; iron